Method for efficiently preparing wood dust biomass fuel - SHEN XIANHUA (2018)
The invention discloses a method for efficiently preparing a wood dust biomass fuel. The method comprises the following steps: a, drying; b, mixing and granulating; and c, compression. Compared with the prior art, the method has the advantages that the prepared wood dust biomass fuel has the density of 1.1-1.2 g/cm , a conventional boiler is adopted, and the combustion efficiency is 25-27%. 本发明公开了种高效木屑生物质燃料的制备方法，包括以下步骤：a、干燥步骤；b、混合制粒步骤；c、压缩步骤。本发明与现有技术相比，所制的木屑生物质燃料的密度为1.1-1.2g/cm，使用通常的锅炉，其燃烧效率为25-27％。